A high-stability biphasic layered cathode for sodium-ion batteries. Issue 23 (19th February 2021) - Liang, Yue; Xu, Hang; Jiang, Kezhu; Bian, Jingjing; Guo, Shaohua; Zhou, Haoshen
Abstract : A P2/O3 Na0.62 Ni0.33 Mn0.62 Sb0.05 O2 composite cathode was synthesized which displays superior rate electrochemical performance compared with its monophasic counterpart Na0.67 Ni0.33 Mn0.67 O2 . P2–O2 phase transition is successfully suppressed and volume strain is extremely small during the electrochemical process. Abstract : A novel biphasic layered Na0.62 Ni0.33 Mn0.62 Sb0.05 O2 cathode is introduced which can be easily synthesized via a solid-state reaction method. Compared with its monophasic counterpart Na0.67 Ni0.33 Mn0.67 O2, biphasic Na0.62 Ni0.33 Mn0.62 Sb0.05 O2 displays a smoother (dis)charge profile, superior rate capability along with splendid cycling performance. Structural and kinetic studies respectively demonstrate extremely small volume strain and rapid charge transfer during the electrochemical process.